Problematika Tafsir Sufi dalam Penafsiran Al Qur’an - Achmad Imam Bashori, bashori; Bashori, Achmad Imam (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2025)
The majority of Quranic scholars consider Quranic interpretation to be synonymous with exoteric interpretation, an interpretation that examines the dzahir aspects of the Quranic verses, even though sometimes the hegemony of exoteric interpretation often becomes an obstacle for other circles or thoughts that have a different perspective, as is the case with Sufi interpretation which specifically examines the messages of the Quran through the esoteric side of the inner meaning of the Quran. This research aims to understand the problems of Sufi interpretation that have been disputed, both in terms of methodology, basic concepts and principles of interpretation. As well as the response and appreciation of the Sufi style of interpretation, as well as its academic and general contribution in addressing the problems of Sufi interpretation. In accordance with the objectives to be achieved, this research method uses a form of qualitative research with the type of library research (library reseacrh), while the descriptive analysis model is used to examine some literature, especially literature related to the study of the interpretation of the Qur'an about the concepts and styles of interpretation of Sufi scholars, along with the response and appreciation of it. This paper briefly produces two important points: First, the explanation of the problems of interpretation that are embedded in Sufi interpretation, including: the orientation of Sufi interpretation with the inner eye (basīrah) which tends to be the interpretation of verses, until it is trapped in the equation of Sufi interpretation with the inner interpretation style (Shi'ah-Ismā'iliyyah tradition), apart from that, the existence of Sufi interpretation is assumed to contradict and even prevent the possibility of the birth of other meanings from the aspect of language (linguistic) and historical dynamics (historical transmission), the tradition of Sufi interpretation is dominated by spiritual inspiration (moral unity), The tradition of Sufi interpretation is dominated by spiritual inspiration (unity of moral, literal, spiritual, and symbolic meaning) so that it does not have a strong methodological basis, the tendency to interpret esoteric verses and ignore the exoteric aspects of the verse, Sufi interpretation is only limited to finding the basic basis of the Qur'anic argumentation to support their thoughts, and suspicion of irregularities in carrying out religious practices that become Sufi rituals (amaliah tasawuf). Second, the explanation of various appreciations and responses along with the arguments against it; ranging from absolute acceptance, acceptance with certain qualifications (conditions and principles), to the stage of complete rejection of Sufi tafsi, so that it requires foresight and sharpness of understanding and classification of Sufi interpretation of Sufi interpretation forms, while still considering its contribution to the interpretation of the Qur'an that cannot be ignored.